Parents Telling Tale Behavior and Children Negative Behavior - Sri Yuni Murti Widayanti (Jurnal Penelitian Kesejahteraan Sosial, 2016)
The research was meant to know the relation between parents telling tale behavior and children’s negative behavior on preschool children. The research took place in Yogyakarta Special Territory. Research subjects were chosen purposively, with category parents having preschool children (<5 years), and parents having telling tale behaviors to their children. Data analyses used product moment program by Sutrisno Hadi results rxy value 0,487 with p value 0,018 and determinant co-efficient 0,229. The result could be meant that the parents telling tale behavior contribution toward their preschool children negative behavior was very meaningful. That meant, children negative behavior could be prevented by parent telling tale behavior from parents to children. Based on the research, recommended to the Ministry of Social Affairs, via Children Social Welfare Directorate, to enhance family empowerment program (through parents telling tale behavior) to build their children as potential next generation to be wise and qualified human resources and having good moral wisdom.